Efficacy of omeprazole, famotidine, mosapride and teprenone in patients with upper gastrointestinal symptoms: an omeprazole-controlled randomized study (J-FOCUS) - Sakurai Kouichi; Nagahara Akihito; Inoue Kazuhiko; Akiyama Junichi; Mabe Katsuhiro; Suzuki Junichi; Habu Yasuki; Araki Akihiro; Suzuki Tsuyoshi; Satoh Katsuaki; Nagami Haruhiko; Harada Ryosaku; et al. (BMC Gastroenterology, 2012)
Abstract Background In Japan, treatment guidelines are lacking for patients with upper gastrointestinal symptoms. We aimed to compare the efficacy of different drugs for the treatment of uninvestigated upper gastrointestinal symptoms. Methods This was a randomized, open-label, parallel-group multicenter study. Helicobacter pylori-negative, endoscopically uninvestigated patients ≥ 20 years of age with upper gastrointestinal symptoms of at least moderate severity (Global Overall Symptom score [GOS] ≥ 4 on a 7-point Likert scale) were randomized to treatment with omeprazole (10 mg once daily), famotidine (10 mg twice daily), mosapride (5 mg three times daily) or teprenone (50 mg three times daily). The primary endpoint was sufficient relief of upper gastrointestinal symptoms after 4 weeks of treatment (GOS ≤ 2). UMIN clinical trial registration number: UMIN000005399. Results Of 471 randomized patients, 454 were included in the full analysis set. After 4 weeks of treatment, sufficient symptom relief was achieved by 66.9% of patients in the omeprazole group, compared with 41.0%, 36.3% and 32.3% in the famotidine, mosapride and teprenone groups, respectively (all, p < 0.001 vs omeprazole). There were no treatment-related adverse events. Conclusions The favorable efficacy and safety profiles of omeprazole in relieving uninvestigated upper gastrointestinal symptoms support its use as first-line treatment in this patient group in Japan. Patients who show no improvement in symptoms despite PPI use, and those with alarm symptoms (such as vomiting, GI bleeding or acute weight loss) should receive further investigation, including prompt referral for endoscopy. Trial registration UMIN000005399.